Extrusion of debris with and without intentional foraminal enlargement – A systematic review and meta‐analysis. (19th June 2021) - Machado, Ricardo; Vigarani, Gislayne; Macoppi, Tainara; Pawar, Ajinkya; Glaci Reinke, Stella Maria; Kovalik Gonçalves, Ana Cristina
Abstract: This systematic review and meta‐analysis was sought to assess whether intentional foraminal enlargement (IFE) is responsible for extrusion of a larger quantity of debris from extracted human teeth with fully formed apexes. Following the recommendations of Preferred Reporting Items for Systematic Review and Meta‐Analysis – PRISMA, electronic and manual searches were performed to identify studies that evaluated the extrusion of debris, comparing different apical limits of instrumentation (with/without IFE). The quality of the studies selected was evaluated, and statistical analysis was conducted. To perform the meta‐analysis, just 3 papers could be used. The heterogeneity was high, however; there was no statistically significant difference in relation to the extrusion of debris in teeth either submitted or not submitted to IFE. The general risk of bias was moderate. In conclusion, IFE is not responsible for extrusion of a larger quantity of debris from extracted human teeth with fully formed apexes.